Implementasi Algoritma C5.0 Untuk Klasifikas Penyakit Gagal Ginjal Kronik - Nurhaningsih, Setyowati; Susanti, Yuliana; Handajani, Sri Sulistijowati (INTEK : Jurnal Informatika dan Teknologi Informasi, 2019)
Chronic kidney failure is one of the deadly diseases in many countries, including in In-donesia. This disease has a prevalence value increasing with the increasing population. Method that can be used to predict chronic kidney failure in the form of classification trees, namely C5.0. The purpose of this study is to apply the C5.0 to the classification of chronic kidney failure and to calculate the accuracy. Method C5.0 is a classification method in selecting its attributes to be processed using gain information. The independ-ent variables that are influential in this study are erythrocytes, urea, creatine, and plate-lets. The results of this study are in the form of a classification tree for chronic kidney failure. The C5.0 method produces 6 classification segments with an accuracy value of 99.3%.